Letter from Georg Bredig and Viktor Homburger to Max Bredig, August 25, 1937 - Bredig, Georg; Homburger, Viktor (1938)
Georg Bredig (1868-1944) gives Max Albert Bredig (1902-1977) stock upon his emigration. The stocks will have to be registered with the Volksverratsgesetz.
Keywords: Bredig, Georg, 1868-1944; Bredig, Max Albert, 1902-1977; Homburger, Viktor, 1888-1968; Emigration and immigration; Stocks; Third Reich